Controllable synthesis of surfactants (PEG and SDS) assisted Copper Selenide Nanoparticles by hydrothermal method for photocatalytic activity. (2022) - Mahendiran, M.; Matharasi, A.; AlindaShaly, A.; Hannah Priya, G.; Mary Linet, J.; Arokiya Mary, T.
Abstract: Semiconductor metal chalcogenide nanomaterials are excellent materials which possess interesting properties like existing in different structures under different conditions of synthesis, layered growth nature, low tunable bandgap and can be grown in ambient environmental conditions, etc. Copper Selenide (Cu2 Se) is an important p-type semiconducting material, with band gaps 1.2–2.3 eV. Copper Selenide has a wide range of applications in various areas of research such as optical filters, super ionic conductors, window materials, thermal electric conductors and photo electric devices. The experimental synthesis of copper selenide was carried out by the hydrothermal route. The size of nanomaterials can be controlled when it is capped with different types of surfactants (cationic, anionic, nonionic or Zwitter ionic). Two types of surfactants, say sodium dodecyl sulphate (SDS), an anionic surfactant and polyethylene glycol (PEG), a non-ionic surfactant were chosen to study their influence on the particle size. The various characterization techniques namely XRD, UV, SEM, TEM, Dielectric studies and photocatalytic activity were adopted to analysis the samples.